Anchoring cobalt oxide nanoparticles on to the surface multiwalled carbon nanotubes for improved supercapacitive performances. Issue 60 (2nd July 2015) - Sankapal, Babasaheb R.; Gajare, Hemant B.; Karade, Swapnil S.; Dubal, Deepak P.
<x xml:space="preserve">Abstract</x> SEM and TEM images of Co3O4 nanodots anchored on to the surface of multiwalled carbon nanotubes.